Foreign direct investments in the time of crisis: FDI inflows to the new EU member states - Folfas, Paweł (Publishing House of the Wrocław University of Economics, 2009)
The first group of studies describes various aspects (positive and negative) of FDI impact on host economies (e.g. [Barrel, Pain 1997; Borensztein et al. 1998; Lim 2001; Moran et al. (eds.) 2005; Oziewicz 2003, pp. 155-178; Zorska 2007, pp. 280-315]). The crucial question is whether and how FDI inflows make influence on economic growth. On the contrary, another group of studies focus on FDI vulnerability to general economic performance (e.g. [Zorska 2007, pp. 33-36]) or to shocks in the world economy such as financial crisis in Asia (e.g. [The Financial Crisis... 1998]) or September 11 events (e.g. [World Investment Report... 2002, p. 5]). Moreover, there are analyses treating FDI as a channel for international trans-mission of disturbances (e.g. [Foreign Direct Investments... 2004]). Finally, there are studies analyzing both growth-driven FDI and FDI-led growth in selected countries (e.g. [Seabra, Flach 2005; Magnus, Fosu 2008]). (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 144-153